A Pilot, Open-Label Study to Evaluate the Efficacy of Intra-Articular Administration of a Caninized TNF Receptor Fc Fusion Protein as a Treatment for Osteoarthritis-Associated Joint Pain - Nakanishi, Aoi; Lascelles, B. Duncan X.; Allen, Julie; Case, Beth; Gearing, David; Enomoto, Masataka (Frontiers in Veterinary Science, 2022)
Tumor necrosis factor-α (TNF-α) is a potential target for osteoarthritis (OA) treatment. In several recent clinical studies in human OA, anti-TNF-α therapy showed promising results; however, these were open-label and based on patient-reported outcome measures. In this study, we developed a caninized TNF-α receptor-Fc (caTNFR-Fc) fusion protein and conducted a non-randomized, open-label, pilot study in dogs with OA using objectively measured ground reaction forces and activity. The aims of the study were to assess the efficacy of the intra-articular (IA) injection of the caTNFR-Fc fusion protein as a treatment for OA pain, and additionally to evaluate TNF concentrations in synovial fluid (SF) between joints with/without OA in dogs. Dogs (n = 12) with single-limb lameness due to single joint appendicular OA were recruited. All dogs received caTNFR-Fc fusion protein injection into the affected joint under sedation. Objective kinetic gait analysis using force plate was performed prior to (baseline), and at 14- and 28-days following treatment. Additionally, SF samples were collected from OA joints (n = 69) and non-OA joints (n = 79) in a different cohort of dogs and TNF-α were measured using enzyme-linked immunosorbent assay. No significant treatment effects on the limb use, activity, and the questionnaire were found. The concentration of TNF-α was significantly higher in OA joints than in healthy joints (p = 0.0019), but TNF-α was detected in only 10/69 OA samples. The IA injection of caTNFR-Fc fusion protein provided no benefit in terms of objective limb use and activity data in dogs with OA in this pilot study. Although the SF concentration of TNF-α was significantly higher in OA joints, few OA joints had measurable TNF-α. Collectively, the data indicate TNF-α may not be a good therapeutic target in canine OA.